Self-efficacy mediates the relationship between grit and life satisfaction in a sample of employed university students resident in the United Arab Emirates - Ektha Benny; Zahir Vally (PLoS ONE, 2026)
Balancing academic and professional responsibilities presents unique psychological challenges for employed university students. Most existing literature on this student population has adopted a deficits-approach. However, identifying the strengths inherent in such individuals could offer valuable avenues for informing strategies to reduce their risk of psychological distress. This study examined whether self-efficacy impacts the relationship between grit and life satisfaction among employed university students in the United Arab Emirates (UAE). A cross-sectional study was employed with data collected from 242 employed university students residing in the UAE. Participants completed a self-report survey that comprised of measurements of grit, self-efficacy and life satisfaction. Grit was significantly and positively associated with both life satisfaction and self-efficacy. Additionally, self-efficacy was found to significantly mediate the relationship between grit and life satisfaction in this sample of participants. This study identified grit as a potential factor that could be harnessed to improve life satisfaction, through the mediating role of self-efficacy. These findings hold important implications for informing strategies to promote positive mental health outcomes among employed university students who possess the strength of grit.